Gaps between supply and demand of acute myocardial infarction treatment in Mexico - Ricardo Pérez-Cuevas; Saúl Eduardo Contreras-Sánchez; Svetlana V Doubova; Sebastián García-Saisó; Odet Sarabia-González; Paulina Pacheco-Estrello; Alexandra Arias-Mendoza (Instituto Nacional de Salud Pública, 2020)
Objective. To analyze acute myocardial infarction (AMI) admissions and in-hospital mortality rates and evaluate the competence of the Ministry of Health (MOH) hospitals to provide AMI treatment. Materials and methods. We used a mixed-methods approach: 1) Joinpoint analysis of hospitalizations and in-hospital mortality trends between 2005 and 2017; 2) a nation-wide cross-sectional MOH hospital survey. Results. AMI hospitalizations are increasing among men and patients aged >60 years; women have higher mortality rates. The survey included 527 hospitals (2nd level =471; 3rd level =56). We identified insufficient competence to diagnose AMI (2nd level 37%, 3rd level 51%), perform pharmacological perfusion (2nd level 8.7%, 3rd level 26.8%), and mechanical reperfusion (2nd level 2.8%, 3rd level 17.9%). Conclusions. There are wide disparities in demand, supply, and health outcomes of AMI in Mexico. It is advisable to build up the competence with gender and age perspectives in order to diagnose and manage AMI and reduce AMI mortality effectively.